2001
DOI: 10.1007/s11661-001-0251-2
|View full text |Cite
|
Sign up to set email alerts
|

The precipitation of the Q phase in an AA6111 Alloy

Abstract: The precipitation behavior of the quaternary Q phase in an Al 6111 alloy has been studied by analytical electron microscopy. The transformation strain associated with the Q phase has been determined from high resolution electron microscopy and electron diffraction. The habit plane of the Q laths is shown to be fully coherent with the Al matrix. The transformation strain is used to explain the pattern of heterogeneous precipitation of the Q phase at dislocations and grain boundaries. The crystal structure and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 53 publications
(21 citation statements)
references
References 17 publications
(6 reference statements)
1
20
0
Order By: Relevance
“…The first factor is related to the observation that the number density of QЈ precipitates is less affected by natural aging, compared to bЉ. As the composition, crystal structure, and structure of the interface are different in bЉ and QЈ, [31,32] one might speculate that the differences in growth rates can be related to the different growth mechanisms for QЈ and bЉ. The larger relative volume fraction of QЈ along with the coarser microstructure results in a slightly lower peak strength for the naturally aged material.…”
Section: Discussionmentioning
confidence: 99%
“…The first factor is related to the observation that the number density of QЈ precipitates is less affected by natural aging, compared to bЉ. As the composition, crystal structure, and structure of the interface are different in bЉ and QЈ, [31,32] one might speculate that the differences in growth rates can be related to the different growth mechanisms for QЈ and bЉ. The larger relative volume fraction of QЈ along with the coarser microstructure results in a slightly lower peak strength for the naturally aged material.…”
Section: Discussionmentioning
confidence: 99%
“…The sample in the test crucible can undergo phase transformations, which either release (exothermic) or consume (endothermic) energy in the form of heat (enthalpy under constant pressure). Nucleation and growth of precipitates is an exothermic reaction that releases energy (heat) from the system to the surroundings, whereas the dissolution of precipitates is endothermic and requires energy from the surrounding [5][6][7][8][9][10][11][12]. The expression of energy for GP zones in the Al-Cu alloys is established by combining the essential Gibbs energy with the interfacial energy and the strain energy.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14][15][16][17] Although it is common in practice to solution treat for up to 16 hours to achieve homogenization within Al grains and spheroidization of the Si plates, the use of much shorter times has been investigated. For example, Parker et al [7] examined changes in microstructure of an Al-Si-Mg alloy with a composition of Al-7Si-0.43Mg-0.02Sr-0.013Fe after solution treating samples at 540°C for times ranging from 10 minutes to 100 hours, and found that spheroidization of eutectic Si was complete in less than 10 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Other workers have obtained similar results for both cast and wrought Al alloys. [10][11][12][13][14][15][16][17] However, it is worth considering that homogenization of cast Al alloys containing Cu is normally a much slower process and would appear to be dictated by the morphology of the cast microstructure. Campbell [18] notes that a time of 40 hours or more is required to facilitate complete homogenization of Al in cast alloys containing Cu, [19] although most Al casting alloys that are heat-treated use solution-treatment times of less than 12 hours.…”
Section: Introductionmentioning
confidence: 99%